Use of Moringa oleífera Lamarck leaf extract as sugarcane juice clarifier: effects on clarifed juice and sugar - Costa, Gustavo Henrique Gravatim [UNESP]; Masson, Igor Dos Santos [UNESP]; Freita, Lidyane Aline De [UNESP]; Roviero, Juliana Pelegrini [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2014)
The objective of this study was to evaluate the effect of Moringa oleifera Lam. leaf extract on the sedimentation of impurities in the treatment of sugarcane juice and the effects on sugar quality and on the clarified juice. The experimental design used was a 4x2 factorial arrangement with four replications. The main treatments performed included the extracted original sugarcane juice, the synthetic polyelectrolyte (Flomex 9076), the leaf extract, and a control. The secondary treatments consisted of the sugarcane varieties RB92579 and RB867515. The clarification process used was simple defecation, in which the flocculating agents and the juice, limed and heated, were poured simultaneously into a decanter. The microbiological and chemico-technological characteristics of the extracted and clarified juices were evaluated. The clarified juice was concentrated up to 60° Brix (syrup) and subjected to boiling in a pilot pan using seeds to perform the graining: The sugar was recovered by centrifugation and analyzed for microbiological and chemico-technological characteristics. It was concluded that the use of the Moringa oleifera Lam. leaves extract resulted in a better quality of clarified juice and sugar.
Keywords: simple defecation; polyelectrolyte; biomolecule; Sedimentation; sucroenergetic sector